From oil to opportunity: Exploring the determinants of non-hydrocarbon growth in Algeria - Larbi, Malika; Blal, Fatima Zahra; Abdelbaki, Hayat; Benhaddou, Amina (The International tax journal, 2025)
The study aims to identify the determinants of economic diversification outside the hydrocarbons sector to achieve economic take-off in Algeria during the period 2000-2023, using the ARDL model. The study concluded that there is no long-term co-integration relationship between the study variables, with a negative impact of the determinants of economic diversification determinants as indicated by the Hirschman-Heyerdahl index. It found that loans directed to the private sector do not contribute to to enhancing investments or expanding business activities in various economic sector. Meanwhile, fixed capital suffers from significant imbalances in the mechanisms of financial resource allocation, as large budgets are allocated for infrastructure development and community facilities, which generate no direct financial returns. This comes at the expanse of postponing or sometimes canceling sspending on productive investments and large wealth-generating projects that could have a high return in stimulating economic growth and diversifying the economy.